Gender Influence on Slang Used by Teenagers in Their Daily Conversation at School - Annisa Salma (Passage, 2013)
The research entitled “Gender Influence on Slang Used by Teenagers in their Daily Conversation at School” aims to investigate types of slang and gender influence on the use of slang among teenagers. Data were collected from observation, questionnaire, and interview. To analyze the data, the theories proposed by Potter (1975) and Kahn Illson (1985) were implemented to identify the types of slang among teenagers, whereas Diekman and Eagly’s (2000) theory was applied to investigate the gender influence on the use of slang among them.The findings show that there were 12 types of slang used by male and female teenagers, such as back, centre, clipping or shortening, blending, compounding, nonsense reduplication, acronyms, loan or borrowing, onomatopoeia, substitution, and two types of slang categorized by Willis (1964). The results of analysis also reveal that gender may affect the use of slang. It can be seen from the total number that slang used by male teenagers (54,3%) tend to be higher than females (45,7%). Therefore, it can be concluded that male teenagers use slang more than females and it can also be understood that the tendency of males to use standard language is to show their machismo.Keywords: Teenagers, Language, Slang, Gender, Sociolinguistics.